Review-Simulation Model of Power Electronic Converters by Using MATLAB - Salam Waley Shneen; Suaad Makki Jiaad (Universitas Ahmad Dahlan, 2026)
Power electronics is known as one of the most important branches of electrical science or electrical engineering, focusing on the design of electronic circuits for control and conversion applications of electrical quantities between the input and output of electronic converters. Power electronics is linked to control (control systems) on the one hand and conversion (electrical energy conversion) on the other. Semiconductors (diodes, transistors, and thyristors) are used in power electronics construction. Industrial applications are one of the most important uses of power electronics. The use of power electronics in many fields provides improved energy use with a high level of efficiency, such as in renewable energies (such as solar panels and wind turbines), as well as electric vehicles and related industrial applications. Converters are named according to their function. Rectifiers convert alternating current (AC) to direct current (DC) in either single-phase or three-phase. Converters are constructed using semiconductors, including diodes, transistors, and thyristors. The number of electronic switches varies depending on the type of converter and is determined by the type of power source and the type of load connected to the converter's output. Another type of converter, called an inverter, works in the opposite direction to a rectifier, converting DC to alternating current in either single-phase or three-phase. To further understand converters, this review presents a literature review of power converters according to research contributions. The first research contribution includes an overview of the power electronics overview. The second research contribution identifies converter types, and the third identifies their applications. To further enhance knowledge, we use theoretical mathematical representations of these types of power converters and select simulation models using MATLAB to analyze their behavior through simulation results. Based on the results, appropriate conclusions can be drawn and contributions can be identified for future work.